Doxorubicin resistance in breast cancer is mediated via the activation of FABP5/PPARγ and CaMKII signaling pathway - Chen, Nan-Nan; Ma, Xin-Di; Miao, Zhuang; Zhang, Xiang-Mei; Han, Bo-Ye; Almaamari, Ahmed Ali; Huang, Jia-Min; Chen, Xue-Yan; Liu, Yun-Jiang; Su, Su-Wen (Frontiers in Pharmacology, 2023)
Breast cancer is the most prevalent malignancy among women. Doxorubicin (Dox) resistance was one of the major obstacles to improving the clinical outcome of breast cancer patients. The purpose of this study was to investigate the relationship between the FABP signaling pathway and Dox resistance in breast cancer. The resistance property of MCF-7/ADR cells was evaluated employing CCK-8, western blot (WB), and confocal microscopy techniques. The glycolipid metabolic properties of MCF-7 and MCF-7/ADR cells were identified using transmission electron microscopy, PAS, and Oil Red O staining. FABP5 and CaMKII expression levels were assessed through GEO and WB approaches. The intracellular calcium level was determined by flow cytometry. Clinical breast cancer patient's tumor tissues were evaluated by immunohistochemistry to determine FABP5 and p-CaMKII protein expression. In the presence or absence of FABP5 siRNA or the FABP5-specific inhibitor SBFI-26, Dox resistance was investigated utilizing CCK-8, WB, and colony formation methods, and intracellular calcium level was examined. The binding ability of Dox was explored by molecular docking analysis. The results indicated that the MCF-7/ADR cells we employed were Dox-resistant MCF-7 cells. FABP5 expression was considerably elevated in MCF-7/ADR cells compared to parent MCF-7 cells. FABP5 and p-CaMKII expression were increased in resistant patients than in sensitive individuals. Inhibition of the protein expression of FABP5 by siRNA or inhibitor increased Dox sensitivity in 2 MCF-7/ADR cells and lowered intracellular calcium, PPARγ, and autophagy.Molecular docking results showed that FABP5 binds more powerfully to Dox than the known drug resistance-associated protein P-GP. In summary, the PPARγ and CaMKII axis mediated by FABP5 plays a crucial role in breast cancer chemoresistance. FABP5 is a potentially targetable protein and therapeutic biomarker for the treatment of Dox resistance in breast cancer.